Kajian Teknis Penerangan Bengkel Produksi Kapal Perang - Fajar Tomie (Mars : Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2023)
Good lighting in a room is an important role that must be fulfilled to create a comfortable, functional and productive atmosphere. Inadequate lighting, such as lighting that is too dim or too bright, can cause eye fatigue, decreased productivity, and even health problems. In designing a room, lighting is also an important aspect that must be considered. Factors such as the type of activities performed in the room, the size of the room, and individual preferences can influence the selection of lamp types, light source placement, and optimal lighting settings.